News Consumption Behaviour of Generation Z in The Reading Community Via Instagram - Fajar Nurjaman (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze and examine the effect of learning methods and learning motivation on the English descriptive text writing skills of vocational high school students in Kuningan Regency. The method used in this study was experimental with the population of grade X students from two SMKs, namely SMK Negeri 6 Brass and SMK Budi Bhakti, involving 60 students as samples. Data were collected through a questionnaire on perception of learning methods, a questionnaire on learning motivation, and a writing skills test. Data analysis was conducted using two-way analysis of variance (ANOVA). The results showed that: 1) There is a significant effect of learning methods on students' English descriptive text writing skills with Sig. = 0.003 < 0.05 and Fh = 9.427. 2) There is a significant effect of learning motivation on students' writing skills with Sig. = 0.000 <0.05 and Fh = 120.422. 3) There is a significant interactive effect between learning methods and learning motivation on students' writing skills with Sig. = 0.035 < 0.05 and Fh = 4.668. This study concludes that learning methods and learning motivation have a significant impact on the English descriptive text writing skills of vocational high school students in Kuningan Regency. The results of this study provide important insights for teachers in designing more effective learning strategies to improve students' writing skills.